Relationship Building as a Strategy for Managing Referring Clinicians. Issue 1 (12th January 2022) - Marshall, Holly; Mehta, Lina; Plecha, Donna
Abstract: The strength of a radiology practice depends on the strong relationships radiologists develop with referring clinicians. Solid relationships with referring clinicians can contribute to a satisfying work environment, and ultimately excellent patient care. There are several different ways that a radiologist can help improve relationships with clinicians. As a start, this includes a radiologist strengthening one's emotional intelligence. Also, identifying the personality traits of others is key to successful interactions. Conflicts in the workplace are inevitable, and effective negotiation is helpful in building relationships with clinicians. Interacting with the referring clinicians is also key to a successful relationship. This includes all in-person communication, participating in tumor boards, community outreach events, and social functions outside of work. This article presents several tips to improve and manage relationships with referring clinicians.